Biomass-derived in-situ nitrogen-phosphorus-doped carbon material loaded iron-based catalyst as well as preparation and application thereof
By using biomass-derived in situ nitrogen-phosphorus doped carbon materials to support mixed valence iron-based photocatalysts, the existing photocatalysts have low activity, serious photocorrosion and poor stability in the photocatalytic reduction CO2 reaction, and an efficient and stable CO2 reduction effect has been achieved.
Patent Information
- Application Number
- CN202411889661.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing photocatalysts have problems such as low activity, serious photocorrosion and poor stability in the photocatalytic reduction CO2 reaction.
Biomass-derived in situ nitrogen-phosphorus doped carbon materials are used to support mixed valence iron-based photocatalysts, and through specific preparation methods, including biomass crushing, magnetic stirring, freeze-drying, microwave treatment, hydrothermal reaction and pyrolytic calcination, to form an efficient photocatalyst.
High photocatalytic performance and good stability are achieved, and CO2 can be effectively reduced to carbon monoxide and methane, and the cycle stability is good, and the yield of the target product is high.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to an in-situ nitrogen and phosphorus doped carbon material loaded with an iron-based catalyst derived from biomass, and its preparation and application in photocatalytic reduction of CO2. Background Art
[0002] Due to the extensive use of fossil fuels, CO2 emissions exceed nature's processing capacity, leading to global warming and posing a threat to the environment and ecology. In order to achieve the "dual carbon goals", many studies are mainly centered on reducing CO2 emissions, capturing CO2, and converting and utilizing CO2. Among them, converting CO2 into high-value-added fuels or chemicals plays an important role in solving energy supply and environmental pollution problems. Researchers usually use thermal catalysis, electrocatalysis, and photocatalysis to achieve this. Compared with thermal catalysis and electrocatalysis, the photocatalytic reduction of CO2 technology using ultraviolet or visible light to generate photogenerated electrons has the advantages of mild operating conditions, low energy consumption, and green and pollution-free. It is the most promising way to achieve the "dual carbon" goals and has attracted widespread attention from researchers.
[0003] However, single semiconductor materials generally have problems such as the band gap width is too wide or too narrow, the light absorption or light response range is insufficient, the photogenerated electron pairs are easy to recombine, the conductivity is poor, and the negative electrode potential is insufficient to reduce CO2, which leads to poor photocatalytic activity and weak stability. Many studies aim to enhance light absorption, modulate the band gap width, increase defect structure, change or modify active centers, accelerate electron transfer, inhibit the recombination of photogenerated electron pairs, and enhance the activation and adsorption of substrate molecules by constructing heterojunctions, plasma modification, composite carbon materials or porous materials, thereby improving photocatalytic activity. For example, Chinese Patent (202110057935.3) improves the photocatalytic performance of CdS by compounding CdS with MOF-808 and RGO to obtain a lower band gap value than pure CdS. Chinese Patent (202011108636.X) uses modified nitrogen-containing defect structure graphitic carbon nitride (gC3N x ) composite iron oxide (Fe2O3) to obtain a Z-type composite catalyst for photocatalytic nitrogen fixation and ammonia production. However, there are still problems such as low photocatalytic activity, severe photocorrosion, and poor catalyst stability.
[0004] Carbon materials are acid-resistant and have good electrical conductivity. Using them as carriers can disperse active components well. In particular, the use of heteroatom-doped carbon materials can significantly improve the electronic structure of carbon materials, forming an electronic structure with uneven charge distribution, which not only enhances its adsorption and activation ability for substrate molecules, but also has an electron density regulating effect on the active components.
[0005] In summary, the technical problems to be solved by the present invention are:
[0006] A method for preparing a biomass-derived in-situ nitrogen-phosphorus-doped carbon material loaded with mixed-valence iron-based photocatalytic material has been developed. The photocatalytic material prepared by this method can be used in the photocatalytic reduction of carbon dioxide reaction, and has high photocatalytic performance and good stability. Summary of the invention
[0007] One of the purposes of the present invention is to provide a method for preparing a biomass-derived in-situ nitrogen-phosphorus-doped carbon material loaded with an iron-based photocatalyst, so as to overcome the problems of the existing nitrogen-phosphorus-doped carbon material preparation method using organic or inorganic chemical reagents as raw materials or activators, such as high cost, complicated steps, uneven doping, and high environmental pressure.
[0008] A second object of the present invention is to provide a biomass-derived in-situ nitrogen-phosphorus-doped carbon material loaded with an iron-based photocatalyst.
[0009] A third object of the present invention is to provide an application of a biomass-derived in-situ nitrogen and phosphorus-doped carbon material loaded with an iron-based photocatalyst in the photocatalytic reduction of CO2.
[0010] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0011] In a first aspect, the present invention provides a method for preparing a biomass-derived in-situ nitrogen and phosphorus-doped carbon material loaded with an iron-based photocatalyst, comprising the following steps:
[0012] The biomass is weighed, crushed and ground to less than 200 meshes, a solvent is added, and after the biomass is fully dispersed and activated, an iron-containing aqueous solution is added, wherein the solute of the iron-containing aqueous solution is iron salt and / or ferrous salt and the total concentration is 0.5-3 mol / L, the mixture is stirred and mixed evenly, and then the pH is adjusted to be greater than 9 with an alkaline reagent to form a gel; the gel is freeze-dried, and then microwave-treated at a power of 400-800 W for 3-5 minutes, and then hydrothermally reacted at 160-200° C. for 8-15 hours, filtered and washed to obtain a precursor; after drying the precursor, the precursor is heated to 700-950° C. in an inert gas atmosphere at a heating rate of 3-15° C., calcined for 0.5-2.5 hours, and cooled to obtain a biomass-derived in-situ nitrogen-phosphorus-doped carbon material loaded with iron-based photocatalyst;
[0013] The biomass is one or more selected from glucose, sucrose, brown sugar, soybean meal, Escherichia coli, yeast, humus, and distiller's grains;
[0014] The alkaline reagent is any one or more of 1-6M ammonia water, 1-6M sodium hydroxide aqueous solution, 1-6M potassium hydroxide aqueous solution, 1-6M sodium carbonate aqueous solution, and 1-6M sodium bicarbonate aqueous solution;
[0015] The feed ratio of the biomass, the solvent and the iron-containing aqueous solution is (2-10) g: (2-25) g: (10-40) mL.
[0016] Preferably, the biomass is one of the following: a mixture of distiller's grains, yeast, soybean meal and humus in a mass ratio of 1:1, and a mixture of distiller's grains and brown sugar in a mass ratio of 5:1.
[0017] Preferably, the solvent is selected from any one of water, ethanol, 1-5 vol% glutaraldehyde aqueous solution, 1-5 vol% formaldehyde aqueous solution, and 1-5 vol% acetone aqueous solution. More preferably, the solvent is selected from any one of water, 5 vol% glutaraldehyde aqueous solution, 3 vol% formaldehyde aqueous solution, and 5 vol% acetone aqueous solution.
[0018] Preferably, the iron salt is any one or more of ferric chloride, ferric sulfate, and ferric nitrate, and the ferrous salt is any one or more of ferrous chloride, ferrous sulfate, ferrous acetate, and ferrous oxalate. More preferably, the solute in the iron-containing aqueous solution is a ferrous salt, further preferably any one of ferrous chloride, ferrous sulfate, and ferrous oxalate, and most preferably ferrous chloride.
[0019] Preferably, the alkaline reagent is any one or more of 4-6M ammonia water, 4-6M sodium hydroxide aqueous solution, 4-6M potassium hydroxide aqueous solution, 4-6M sodium carbonate aqueous solution, and 4-6M sodium bicarbonate aqueous solution.
[0020] Preferably, the feed ratio of the biomass, the solvent and the iron-containing aqueous solution is (5-10) g: (20-30) g: 15 mL.
[0021] Preferably, the biomass is fully dispersed and activated by weighing the biomass, crushing and grinding it to less than 200 mesh (more preferably 100-200 mesh), adding a solvent, ultrasonicating for 3-5 minutes, and then standing for 30-60 minutes.
[0022] Preferably, the freeze drying is performed by vacuum drying at -10 to -50°C for 8 to 12 hours.
[0023] Preferably, the washing is: first washing with deionized water until neutral, and then washing thoroughly with ethanol.
[0024] Preferably, the precursor is dried at 80-100°C.
[0025] Preferably, the temperature is raised to 750-850° C. at a rate of 3-10° C. / min in a nitrogen atmosphere and calcined for 1-2 hours. More preferably, the temperature is raised to 750-850° C. at a rate of 5-10° C. / min in a nitrogen atmosphere and calcined for 1-2 hours.
[0026] A particularly preferred set of technical solutions of the present invention is: the biomass is vinasse or yeast, the solvent is 3% formaldehyde aqueous solution, 5% glutaraldehyde aqueous solution or 5% acetone aqueous solution, the iron-containing aqueous solution is 1.5M ferrous chloride aqueous solution, the alkaline reagent is 5M KOH aqueous solution or 5M ammonia water, the temperature is raised to 750-850°C in a nitrogen atmosphere at a rate of 3-10°C / min, and calcined for 1-2h; the feed ratio of the biomass, solvent and iron-containing aqueous solution is 5-10g:20g:15mL. Most preferably: the biomass is vinasse, the solvent is 3% formaldehyde aqueous solution, the iron-containing aqueous solution is 1.5M ferrous chloride aqueous solution, the alkaline reagent is 5M KOH aqueous solution or 5M ammonia water, the temperature is raised to 850°C in a nitrogen atmosphere at a rate of 8-10°C / min, and calcined for 1-1.5h; the feed ratio of the biomass, solvent and iron-containing aqueous solution is 5-10g:20g:15mL.
[0027] Another particularly preferred embodiment of the present invention is: the biomass is a mixture of soybean meal and humus in a mass ratio of 1:1, the solvent is water, the iron-containing aqueous solution is a 2.0M ferrous oxalate aqueous solution, the alkaline reagent is 6M ammonia water, the temperature is raised to 750°C in a nitrogen atmosphere at a rate of 5°C / min, and calcined for 2h; the feed ratio of the biomass, the solvent and the iron-containing aqueous solution is 6g:30g:15mL.
[0028] In a second aspect, the present invention provides a biomass-derived in-situ nitrogen and phosphorus-doped carbon material loaded with iron-based photocatalyst prepared according to the preparation method described in the first aspect.
[0029] The biomass-derived in-situ nitrogen and phosphorus-doped carbon material-loaded iron-based photocatalyst of the present invention contains zero-valent, divalent and trivalent iron at the same time.
[0030] In a third aspect, the present invention provides the use of the biomass-derived in-situ nitrogen and phosphorus-doped carbon material loaded with an iron-based photocatalyst in the photocatalytic reduction of CO2 as described in the second aspect.
[0031] Preferably, the specific operating steps of the application are: weighing the biomass-derived in-situ nitrogen and phosphorus-doped carbon material loaded with iron-based photocatalyst and sodium bicarbonate into a reactor, slowly adding sulfuric acid, stirring to make it evenly dispersed, and generating CO2 and water in situ; then reacting under visible light for 1 to 3 hours to generate CO and methane.
[0032] Preferably, the catalyst can achieve higher CO and methane yields.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The present invention uses biomass containing carbon, nitrogen and phosphorus elements as raw materials to obtain nitrogen and phosphorus co-doped carbon materials. After the biomass is mixed with iron salts, a "one-pot method" is used to obtain in situ nitrogen and phosphorus doped carbon materials loaded with mixed valence iron-based photocatalytic materials through various heat treatments. The raw materials are widely available, low in cost, and the preparation method is simple and green.
[0035] (2) During the preparation process, no additional nitrogen or phosphorus source is required, no reducing agent, no chemical activating agent, etc. The operation is simple and convenient, with little pollution, and is suitable for large-scale production and promotion and application.
[0036] (3) The freeze-drying technology, microwave heat treatment, hydrothermal and pyrolysis technologies are combined to assist crystal growth and biomass pore protection to provide guarantees for the formation of the catalyst phase structure.
[0037] (4) During the preparation process of the present invention, biomass and metal ions interact with each other, and heterojunctions are formed between carbon materials and iron oxides and multivalent iron oxides. In particular, the in-situ formation of zero-valent iron assists the rapid transfer of electrons, constructs a multi-site synergistic effect of the catalyst, is beneficial to the separation of electrons and holes, and enables more efficient transfer and utilization of electrons. In addition, the introduction of nitrogen and phosphorus doped carbon materials increases the specific surface area of the catalyst, which is more conducive to the adsorption of substrate molecules.
[0038] (5) The nitrogen and phosphorus doped carbon material loaded with mixed valence iron-based photocatalytic material obtained by the method of the present invention has excellent performance and magnetism, and can be used as a photocatalyst to reduce CO2 to carbon monoxide and methane. It has good cycle stability and a high yield of the target product. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a SEM image of the nitrogen and phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material prepared in Example 1, which shows that the morphology of the material is rod-shaped.
[0040] Figure 2 This is a TEM image of the nitrogen-phosphorus-doped carbon material loaded with mixed-valence iron-based photocatalytic material prepared in Example 1. The image shows that the particles in the material are loaded or embedded in the carbon layer. High-magnification TEM found that the particles are polycrystals of metal elements and metal oxides.
[0041] Figure 3 This is an X-ray diffraction spectrum of the nitrogen and phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material prepared in Example 1, which shows that the material contains elemental iron, iron phosphide, ferrous oxide, ferrosoferric oxide and ferric oxide.
[0042] Figure 4 This is a Raman spectrum of the nitrogen and phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material prepared in Example 1, which shows the presence of graphitic carbon and amorphous carbon in the material as well as Fe-O and Fe-Fe bonds.
[0043] Figure 5 This is the XPS graph of the nitrogen and phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material prepared in Example 1, wherein a: broad spectrum; b: fine spectrum of Fe 2p; the graph shows that the material contains C, N, O, P and Fe elements, including iron, iron phosphide, ferrous oxide, ferrosoferric oxide and ferric oxide.
[0044] Figure 6 This is the EDS element mapping analysis diagram of the nitrogen and phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material prepared in Example 1, which are C, N, O, P and Fe elements and their contents respectively. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described below in conjunction with the accompanying drawings and the best embodiment, but the protection scope of the present invention is not limited thereto:
[0046] In the examples, biomass is vinasse unless otherwise specified, and the biomass is crushed and ground to 100-200 mesh, and the solvent is 3 vol% formaldehyde aqueous solution unless otherwise specified. The amounts used in the photocatalytic reduction of CO2 reaction are as follows: 0.84 g sodium bicarbonate, 3.5 mL 2M sulfuric acid.
[0047] Example 1
[0048] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0049] Weigh 5g of biomass (its elemental composition is shown in Table 1), add 20g of solvent, ultrasonicate for 5min, let stand for 35min, add 15mL of ferrous chloride (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, use 5mol / LKOH to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, then add 10mL of deionized water to the mixture and transfer it to a hydrothermal reactor for hydrothermal heating at 200℃ for 10h to obtain a solid-liquid mixture, filter it under reduced pressure, wash it with deionized water to neutrality, wash it with ethanol 5 times, dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 850℃ at a rate of 10℃ / min in a nitrogen atmosphere, calcine it for 1.5h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 1.
[0050] Table 1 shows the relative contents of various elements in the biomass of Example 1
[0051] element Wt% C 50 N 10 O 30 P 6 Mg 0.01 Na 0.21 K 3.38 Cl 0.4 total 100.00
[0052] Figure 1 This is a SEM image of catalyst 1 prepared in Example 1, which shows that the morphology of the material is rod-shaped.
[0053] Figure 2 This is a TEM image of catalyst 1 prepared in Example 1, which shows that the particles in the material are loaded or embedded in the carbon layer. High-magnification TEM reveals that the particles are single metals and polycrystals of metal oxides.
[0054] Figure 3 This is the X-ray diffraction spectrum of the catalyst 1 prepared in Example 1, which shows that the material contains iron, iron phosphide, ferrous oxide, ferrosoferric oxide and ferric oxide.
[0055] Figure 4 This is a Raman spectrum of catalyst 1 prepared in Example 1, which shows that the material contains graphite carbon and amorphous carbon as well as Fe-O and Fe-Fe bonds.
[0056] Figure 5 This is the XPS graph of catalyst 1 prepared in Example 1, which shows that the material contains C, N, O, P and Fe elements, including iron, iron phosphide, ferrous oxide, ferrosoferric oxide and ferric oxide.
[0057] Figure 6 This is the EDS element mapping analysis chart of catalyst 1 prepared in Example 1, which shows the elements and contents of C, N, O, P and Fe.
[0058] 2. Application of catalyst 1 in photocatalytic carbon dioxide reduction reaction.
[0059] Weigh 0.02 g of catalyst 1, add sodium bicarbonate (0.84 g), evacuate the system, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0060] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0061] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 3.4 μmol g -1 h -1 and 2.8 μmol g -1 h -1 .
[0062] Catalyst 1 was recovered and recycled, and the results are shown in Table 2:
[0063] Table 2 Catalyst 1 Cyclic Application
[0064] frequency <![CDATA[CO production rate (μmolh -1 g -1 )]]> <![CDATA[CH4 production rate (μmolh -1 g -1 )]]> 1 2.8 3.4 2 2.8 3.4 3 2.8 3.4 4 2.8 3.4 5 2.8 3.4 6 2.8 3.4
[0065] Comparative Example 1
[0066] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0067] Weigh 5g of biomass, add 20g of solvent, ultrasonicate for 5min, let stand for 35min, add 15mL of ferric chloride (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, use 5mol / LKOH to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 200℃ for 10h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, and dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 850℃ at a rate of 10℃ / min in a nitrogen atmosphere, calcine it for 1.5h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh) to prepare catalyst 2.
[0068] 2. Application of catalyst 2 in photocatalytic carbon dioxide reduction reaction.
[0069] Weigh 0.02 g of catalyst 2, add sodium bicarbonate (0.84 g), evacuate, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ. Then react under light (300 W xenon lamp simulated sunlight) for 2 h.
[0070] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 2.7 μmol g -1 h -1 and 1.5 μmol g -1 h -1 .
[0071] Comparative Example 2
[0072] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0073] Weigh 5g of sucrose, add 20g of solvent, ultrasonicate for 5min, let stand for 35min, add 15mL of ferrous chloride (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, use 5mol / LKOH to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 200℃ for 10h to obtain a black solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality and ethanol for 5 times, the obtained solid is dried in a vacuum oven at 100℃, transferred to a tubular furnace, and then heated to 850℃ at a rate of 10℃ / min in a nitrogen atmosphere, calcined for 1.5h, and cooled to obtain a black powder. The powder is taken out and ground and sieved (100 mesh) to prepare catalyst 3.
[0074] 2. Application of catalyst 3 in photocatalytic carbon dioxide reduction reaction.
[0075] Weigh 0.02 g of catalyst 3, add sodium bicarbonate (0.84 g), evacuate the system, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0076] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0077] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 1.0 μmol g -1 h -1 and 0.5 μmol g -1 h -1 .
[0078] Comparative Example 3
[0079] 1. A method for preparing an iron-based photocatalytic material:
[0080] 20g solvent, ultrasonic for 5min, let stand for 35min, add 15mL ferrous chloride (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, use 5mol / LKOH to adjust the pH to greater than 9 to form a green gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL deionized water to a hydrothermal reactor and hydroheat it at 200℃ for 10h to obtain a mixture, filter it under reduced pressure, wash it with deionized water to neutrality, wash it with ethanol for 5 times, dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 850℃ at a rate of 10℃ / min in a nitrogen atmosphere, calcine it for 1.5h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 4.
[0081] 2. Application of catalyst 4 in photocatalytic carbon dioxide reduction reaction.
[0082] Weigh 0.02 g of catalyst 4, add sodium bicarbonate (0.84 g), evacuate the system, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0083] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0084] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 0.1 μmol g -1 h -1 and 0.2 μmol g -1 h -1 .
[0085] The heat treatment conditions were changed based on Example 1, as shown in Comparative Examples 4-6.
[0086] Comparative Example 4
[0087] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0088] Weigh 5 g of biomass, add 20 g of solvent, ultrasonicate for 5 min, let stand for 35 min, add 15 mL of ferrous chloride (1.5 mol / L), stir and mix evenly, magnetically stir at 40 ° C for 11 h, use 5 mol / L KOH to adjust the pH to greater than 9 to form a gel, and vacuum dry the mixture at -50 ° C for 10 h. Then transfer the mixture with 10 mL of deionized water to a hydrothermal reactor and hydrotherm at 200 ° C for 10 h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality and ethanol for 5 times, the obtained solid is dried in a vacuum oven at 100 ° C, transferred to a tubular furnace, and then heated to 850 ° C at a rate of 10 ° C / min in a nitrogen atmosphere. Calcinate for 1.5 h, cool to obtain a black powder, take out and grind and sieve (100 mesh), and prepare catalyst 5.
[0089] 2. Application of catalyst 5 in photocatalytic carbon dioxide reduction reaction.
[0090] Weigh 0.02 g of catalyst 5, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0091] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0092] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 0.2 μmol g -1 h -1 and 0.9 μmol g -1 h -1 .
[0093] Comparative Example 5
[0094] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0095] Weigh 5 g of biomass, add 20 g of solvent, ultrasonicate for 5 min, let stand for 35 min, add 15 mL of ferrous chloride (1.5 mol / L), stir and mix evenly, magnetically stir at 40 ° C for 11 h, use 5 mol / L KOH to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50 ° C for 10 h, put it in a microwave oven (power 500 W) and microwave for 3 min to obtain a black solid-liquid mixture, filter it under reduced pressure, and wash it with deionized water to neutrality, wash it with ethanol 5 times, and dry the obtained solid in a vacuum oven at 100 ° C, transfer it to a tubular furnace, and then heat it to 850 ° C at a rate of 10 ° C / min in a nitrogen atmosphere, calcine it for 1.5 h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh) to prepare catalyst 6.
[0096] 2. Application of catalyst 6 in photocatalytic carbon dioxide reduction reaction.
[0097] Weigh 0.02 g of catalyst 6, add sodium bicarbonate (0.84 g), evacuate the system, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0098] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0099] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 0 μmol g -1 h -1 and 0.2 μmol g -1 h -1 .
[0100] Comparative Example 6
[0101] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0102] Weigh 5 g of biomass, add 20 g of solvent, ultrasonicate for 5 min, let stand for 35 min, add 15 mL of ferrous chloride (1.5 mol / L), stir to mix evenly, magnetically stir at 40 ° C for 11 h, use 5 mol / L KOH to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50 ° C for 10 h, transfer it to a tubular furnace, and then heat it to 850 ° C at a rate of 10 ° C / min in a nitrogen atmosphere, calcine it for 1.5 h, and obtain a black powder after cooling. Take it out and grind and sieve it (100 mesh), and prepare catalyst 7.
[0103] 2. Application of catalyst 7 in photocatalytic carbon dioxide reduction reaction.
[0104] Weigh 0.02 g of catalyst 7, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0105] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0106] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 1.7 μmol g -1 h -1 and 0.9 μmol g -1 h -1 .
[0107] Table 3 Effect of heat treatment method
[0108] Heat treatment method <![CDATA[CH4 production rate (μmolg -1 h -1 )]]> <![CDATA[CO production rate (μmolg -1 h -1 )]]> Example 1 Microwave + hydrothermal + pyrolysis 3.4 2.8 Comparative Example 4 Hydrothermal + Pyrolysis 0.2 0.9 Comparative Example 5 Microwave + Pyrolysis 0 0.2 Comparative Example 6 Pyrolysis 1.7 0.9
[0109] Example 2
[0110] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0111] Weigh 3g soybean powder and 3g humus, add 30g water, ultrasonicate for 5min, let stand for 40min, add 15mL ferrous oxalate (2.0mol / L), stir and mix evenly, magnetically stir at 40℃ for 10h, adjust the pH to greater than 9 with 6mol / L ammonia water to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 5min, and then transfer the mixture with 10mL deionized water to a hydrothermal reactor and hydroheat it at 200℃ for 10h to obtain a solid-liquid mixture. After vacuum filtration, wash it with deionized water to neutrality and ethanol for 5 times. After drying the obtained solid in a vacuum oven at 80℃, transfer it to a tubular furnace, and then heat it to 650℃ at a rate of 5℃ / min in a nitrogen atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve it (100 mesh), the prepared catalyst 8.
[0112] 2. Application of catalyst 8 in photocatalytic carbon dioxide reduction reaction.
[0113] Weigh 0.02 g of catalyst 8, add sodium bicarbonate (0.84 g), evacuate the system, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0114] Then react under light (300W xenon lamp simulated sunlight) for 3 hours.
[0115] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 1.4 μmol g -1 h -1 and 0.8 μmol g -1 h -1 .
[0116] Example 3
[0117] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0118] Weigh 3g of soybean powder and 3g of humus, add 30g of water, ultrasonicate for 5min, let stand for 40min, add 15mL of ferrous oxalate (2.0mol / L), stir and mix evenly, magnetically stir at 40℃ for 10h, use 6mol / L ammonia water to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 5min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 200℃ for 10h to obtain a black solid-liquid mixture. After reduced pressure filtration, wash it with deionized water to neutrality, wash it with ethanol 5 times, and dry the obtained solid in a vacuum oven at 80℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 5℃ / min in a nitrogen atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 9.
[0119] 2. Application of catalyst 9 in photocatalytic carbon dioxide reduction reaction.
[0120] Weigh 0.02 g of catalyst 9, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0121] Then react under light (300W xenon lamp simulated sunlight) for 3 hours.
[0122] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 3.0 μmol g -1 h -1 and 2.4 μmol g -1 h -1 .
[0123] Example 4
[0124] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0125] Weigh 3g soybean powder and 3g humus, add 30g water, ultrasonicate for 5min, let stand for 40min, add 15mL ferrous oxalate (2.0mol / L), stir and mix evenly, magnetically stir at 40℃ for 10h, adjust the pH to greater than 9 with 6mol / L ammonia water to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 5min, and then transfer the mixture with 10mL deionized water to a hydrothermal reactor and hydroheat it at 200℃ for 10h to obtain a black solid-liquid mixture. After reduced pressure filtration, wash it with deionized water to neutrality, wash it with ethanol 5 times, and dry the obtained solid in a vacuum oven at 80℃, transfer it to a tubular furnace, and then heat it to 850℃ at a rate of 5℃ / min in a nitrogen atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve it (100 mesh). The prepared catalyst 10.
[0126] 2. Application of catalyst 10 in photocatalytic carbon dioxide reduction reaction.
[0127] 0.02 g of catalyst 10 was weighed, sodium bicarbonate (0.84 g) was added, vacuum was applied, and 3.5 mL of 2 M sulfuric acid was added to generate CO2 and water in situ.
[0128] Then react under light (300W xenon lamp simulated sunlight) for 3 hours.
[0129] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.9 μmol g -1 h -1 and 1.5 μmol g -1 h -1 .
[0130] Example 5
[0131] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0132] Weigh 3g soybean powder and 3g humus, add 30g water, ultrasonicate for 5min, let stand for 40min, add 15mL ferrous oxalate (2.0mol / L), stir and mix evenly, magnetically stir at 40℃ for 10h, use 6mol / L ammonia water to adjust the pH to greater than 9 to form a gel, put it into a microwave oven (power 500W) for microwave 5min, and then vacuum dry the mixture at -50℃ for 10h, and then transfer the mixture with 10mL deionized water to a hydrothermal reactor and hydroheat at 200℃ for 10h to obtain a solid-liquid mixture, filter it under reduced pressure, and wash it with deionized water to neutrality, wash it with ethanol 5 times, and dry the obtained solid in a vacuum oven at 80℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 5℃ / min in an argon atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 11.
[0133] 2. Application of catalyst 11 in photocatalytic carbon dioxide reduction reaction.
[0134] Weigh 0.02 g of catalyst 11, add sodium bicarbonate (0.84 g), evacuate the system, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0135] Then react under light (300W xenon lamp simulated sunlight) for 3 hours.
[0136] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 3.0 μmol g -1 h -1 and 2.4 μmol g -1 h -1 .
[0137] Table 4 Effect of pyrolysis conditions
[0138]
[0139]
[0140] Example 6
[0141] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0142] Weigh 5g of wine lees and 1g of brown sugar, add 20g of water, ultrasonicate for 5min, let stand for 40min, add 15mL of ferric nitrate (1.5mol / L), stir and mix evenly, magnetically stir at 30℃ for 13h, use 4mol / L ammonia water to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 5min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 180℃ for 12h to obtain a solid-liquid mixture. After reduced pressure filtration, wash with deionized water to neutrality, wash with ethanol 5 times, and dry the obtained solid in a vacuum oven at 80℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 3℃ / min in an argon atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 12.
[0143] 2. Application of catalyst 12 in photocatalytic carbon dioxide reduction reaction.
[0144] Weigh 0.02 g of catalyst 12, add sodium bicarbonate (0.84 g), evacuate the system, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0145] Then react under light (300W xenon lamp simulated sunlight) for 3 hours.
[0146] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 2.1 μmol g -1 h -1 and 3.0 μmol g -1 h -1 .
[0147] Example 7
[0148] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0149] Weigh 5g of wine lees and 1g of brown sugar, add 20g of water, ultrasonicate for 5min, let stand for 40min, add 15mL of ferric nitrate (1.5mol / L), stir and mix evenly, magnetically stir at 30℃ for 13h, adjust the pH to greater than 9 with 2mol / L ammonia water to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 5min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 180℃ for 12h to obtain a black solid-liquid mixture. After vacuum filtration, wash it with deionized water until neutral, wash it with ethanol 5 times, and dry the obtained solid in a vacuum oven at 80℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 3℃ / min in an argon atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve it (100 mesh), the prepared catalyst 13.
[0150] 2. Application of catalyst 13 in photocatalytic carbon dioxide reduction reaction.
[0151] Weigh 0.02 g of catalyst 13, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0152] Then react under light (300W xenon lamp simulated sunlight) for 3 hours.
[0153] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.7 μmol g -1 h -1 and 2.4 μmol g -1 h -1 .
[0154] Example 8
[0155] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0156] Weigh 5g of wine lees and 1g of brown sugar, add 20g of water, ultrasonicate for 5min, let stand for 40min, add 15mL of ferric nitrate (1.5mol / L), stir and mix evenly, magnetically stir at 30℃ for 13h, use 6mol / L ammonia water to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 5min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 180℃ for 12h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, and dry the obtained solid in a vacuum oven at 80℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 3℃ / min in an argon atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 14.
[0157] 2. Application of catalyst 14 in photocatalytic carbon dioxide reduction reaction.
[0158] Weigh 0.02 g of catalyst 14, add sodium bicarbonate (0.84 g), evacuate the system, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0159] Then react under light (300W xenon lamp simulated sunlight) for 3 hours.
[0160] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.6 μmol g -1 h -1 and 2.3 μmol g -1 h -1 .
[0161] Example 9
[0162] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0163] Weigh 5g of vinasse and 1g of brown sugar, add 20g of water, ultrasonicate for 5min, let stand for 40min, add 15mL of ferric nitrate (1.5mol / L), stir and mix evenly, magnetically stir at 30℃ for 13h, use 2mol / L sodium hydroxide to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 5min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 180℃ for 12h to obtain a solid-liquid mixture. After vacuum filtration, wash it with deionized water to neutrality and ethanol for 5 times. After drying the obtained solid in a vacuum oven at 80℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 3℃ / min in an argon atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve it (100 mesh), the prepared catalyst 15.
[0164] 2. Application of catalyst 15 in photocatalytic carbon dioxide reduction reaction.
[0165] Weigh 0.02 g of catalyst 15, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0166] Then react under light (300W xenon lamp simulated sunlight) for 3 hours.
[0167] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.9 μmol g -1 h -1 and 2.3 μmol g -1 h -1 .
[0168] Example 10
[0169] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0170] Weigh 5g of wine lees and 1g of brown sugar, add 20g of water, ultrasonicate for 5min, let stand for 40min, add 15mL of ferric nitrate (1.5mol / L), stir and mix evenly, magnetically stir at 30℃ for 13h, use 2mol / L sodium carbonate to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 5min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 180℃ for 12h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, and dry the obtained solid in a vacuum oven at 80℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 3℃ / min in an argon atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 16.
[0171] 2. Application of catalyst 16 in photocatalytic carbon dioxide reduction reaction.
[0172] Weigh 0.02 g of catalyst 16, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0173] Then react under light (300W xenon lamp simulated sunlight) for 3 hours.
[0174] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 1.0 μmol g -1 h -1 and 2.2 μmol g -1 h -1 .
[0175] Embodiment 11
[0176] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0177] Weigh 5g of wine lees and 1g of brown sugar, add 20g of water, ultrasonicate for 5min, let stand for 40min, add 15mL of ferric nitrate (1.5mol / L), stir and mix evenly, magnetically stir at 30℃ for 13h, use 2mol / L sodium carbonate to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 5min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 180℃ for 12h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, and dry the obtained solid in a vacuum oven at 80℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 3℃ / min in an argon atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 17.
[0178] 2. Application of catalyst 17 in photocatalytic carbon dioxide reduction reaction.
[0179] Weigh 0.02 g of catalyst 17, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0180] Then react under light (300W xenon lamp simulated sunlight) for 3 hours.
[0181] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.6 μmol g -1 h -1 and 2.5 μmol g -1 h -1 .
[0182] Table 5 Effect of alkali type and concentration
[0183] Alkali (concentration) <![CDATA[CH4 production rate (μmolg -1 h -1 )]]> <![CDATA[CO production rate (μmolg -1 h -1 )]]> Example 6 Ammonia (4M) 2.1 3.0 Example 7 Ammonia (2M) 0.7 2.4 Example 8 Ammonia (6M) 0.6 2.3 Example 9 Sodium hydroxide (2M) 0.9 2.3 Example 10 Sodium carbonate (2M) 1.0 2.2 Embodiment 11 Sodium bicarbonate (2M) 0.6 2.5
[0184] Example 12
[0185] 1. Cycling experiment of catalyst 1 in photocatalytic carbon dioxide reduction reaction.
[0186] The catalyst from Example 1 was recovered and washed several times with 30 mL of ethanol and deionized water, respectively. After drying in a vacuum oven, the photocatalytic carbon dioxide reduction reaction of Example 1 was continued for a cycle experiment. After six cycles, the CH4 or CO yield was calculated. The CH4 and CO production rates were 3.4 μmol g -1 h -1 and 2.8 μmol g -1 h -1(As shown in Table 2).
[0187] Example 13
[0188] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0189] Weigh 10g of yeast, add 20g of 5% acetone aqueous solution, ultrasonicate for 5min, let stand for 35min, add 15mL of ferrous chloride (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, use 5mol / L ammonia water to adjust the pH to greater than 9 to form a green gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 150℃ for 10h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 850℃ at a rate of 8℃ / min in a nitrogen atmosphere, calcine it for 1h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 18.
[0190] 2. Application of catalyst 18 in photocatalytic carbon dioxide reduction reaction.
[0191] Weigh 0.03 g of catalyst 18, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0192] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0193] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 3.0 μmol g -1 h -1 and 2.7 μmol g -1 h -1 .
[0194] Embodiment 14
[0195] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0196] Weigh 10g of soybean powder, add 20g of 5% acetone aqueous solution, ultrasonicate for 5min, let stand for 35min, add 15mL of ferrous chloride (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, use 5mol / L ammonia water to adjust the pH to greater than 9 to form a green gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 150℃ for 10h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, and dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 850℃ at a rate of 8℃ / min in a nitrogen atmosphere, calcine it for 1h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 19.
[0197] 2. Application of catalyst 19 in photocatalytic carbon dioxide reduction reaction.
[0198] Weigh 0.03 g of catalyst 19, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0199] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0200] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 1.0 μmol g -1 h -1 and 1.4 μmol g -1 h -1 .
[0201] Embodiment 15
[0202] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0203] Weigh 10g of humus, add 20g of 5% acetone aqueous solution, ultrasonicate for 5min, let stand for 35min, add 15mL of ferrous chloride (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, adjust the pH to greater than 9 with 5mol / L ammonia water to form a green gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 150℃ for 10h to obtain a solid-liquid mixture, filter it under reduced pressure, wash it with deionized water to neutrality, wash it with ethanol 5 times, dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 850℃ at a rate of 8℃ / min in a nitrogen atmosphere, calcine it for 1h, and obtain a black powder after cooling. Take it out and grind and sieve it (100 mesh). The prepared catalyst 20.
[0204] 2. Application of catalyst 20 in photocatalytic carbon dioxide reduction reaction.
[0205] Weigh 0.03 g of catalyst 20, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0206] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0207] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 1.5 μmol g -1 h -1 and 2.0 μmol g -1 h -1 .
[0208] Example 16
[0209] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0210] Weigh 10g of wine lees, add 20g of 5% acetone aqueous solution, ultrasonicate for 5min, let stand for 35min, add 15mL of ferrous chloride (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, adjust the pH to greater than 9 with 5mol / L ammonia water to form a green gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 150℃ for 10h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 850℃ at a rate of 8℃ / min in a nitrogen atmosphere, calcine it for 1h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 21.
[0211] 2. Application of catalyst 21 in photocatalytic carbon dioxide reduction reaction.
[0212] Weigh 0.03 g of catalyst 21, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0213] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0214] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 3.0 μmol g -1 h -1 and 2.9 μmol g -1 h -1 .
[0215] Embodiment 17
[0216] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0217] Weigh 10g of glucose, add 20g of 5% acetone aqueous solution, ultrasonicate for 5min, let stand for 35min, add 15mL of ferrous chloride (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, use 5mol / L ammonia water to adjust the pH to greater than 9 to form a green gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 150℃ for 10h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 850℃ at a rate of 8℃ / min in a nitrogen atmosphere, calcine it for 1h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 22.
[0218] 2. Application of catalyst 22 in photocatalytic carbon dioxide reduction reaction.
[0219] Weigh 0.03 g of catalyst 22, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0220] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0221] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 2.5 μmol g -1 h -1 and 2.1 μmol g -1 h -1 .
[0222] Table 6 Effects of different biomass
[0223] Biomass <![CDATA[CH4 production rate (μmolg -1 h -1 )]]> <![CDATA[CO production rate (μmolg -1 h -1 )]]> Embodiment 13 Yeast 3.0 2.7 Embodiment 14 Soybean flour 1.0 1.4 Embodiment 15 humus 1.5 2.0 Example 16 Lees 3.0 2.9 Embodiment 17 glucose 0.5 1.0 Comparative Example 3 none 0.1 0.2
[0224] Embodiment 18
[0225] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0226] Weigh 10g of wine lees, add 20g of 5% glutaraldehyde aqueous solution, ultrasonicate for 5min, let stand for 35min, add 15mL of ferrous chloride (0.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, adjust the pH to greater than 9 with 5mol / L ammonia water to form a green gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 200℃ for 10h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 3℃ / min in a nitrogen atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh) to prepare catalyst 23.
[0227] 2. Application of catalyst 23 in photocatalytic carbon dioxide reduction reaction.
[0228] Weigh 0.03 g of catalyst 23, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0229] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0230] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 0.6 μmol g -1 h -1 and 0.8 μmol g -1 h -1 .
[0231] Embodiment 19
[0232] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0233] Weigh 10g of vinasse, add 20g of 5% glutaraldehyde aqueous solution, ultrasonicate for 5min, let stand for 35min, add 15mL of ferrous chloride (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, adjust the pH to greater than 9 with 5mol / L ammonia water to form a green gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 200℃ for 10h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 3℃ / min in a nitrogen atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 24.
[0234] 2. Application of catalyst 24 in photocatalytic carbon dioxide reduction reaction.
[0235] Weigh 0.03 g of catalyst 24, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0236] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0237] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 2.9 μmol g -1 h -1 and 3.0 μmol g -1 h -1 .
[0238] Embodiment 20
[0239] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0240] Weigh 10g of vinasse, add 20g of 5% glutaraldehyde aqueous solution, ultrasonicate for 5min, let stand for 35min, add 15mL of ferrous chloride (2.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, adjust the pH to greater than 9 with 5mol / L ammonia water to form a green gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 200℃ for 10h to obtain a black solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 3℃ / min in a nitrogen atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh), the prepared catalyst 25.
[0241] 2. Application of catalyst 25 in photocatalytic carbon dioxide reduction reaction.
[0242] Weigh 0.03 g of catalyst 25, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0243] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0244] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C). The CH4 or CO yield was calculated. The CH4 and CO production rates were 0.5 μmol g -1 h -1 and 2.3 μmol g -1 h -1 .
[0245] Embodiment 21
[0246] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0247] Weigh 10 g of vinasse, add 20 g of 5% glutaraldehyde aqueous solution, ultrasonicate for 5 min, let stand for 35 min, add 15 mL of ferrous sulfate (1.5 mol / L), stir and mix evenly, magnetically stir at 40°C for 11 h, use 2 mol / L sodium hydroxide to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50°C for 10 h, put it in a microwave oven (power 500 W) for 3 min, and then transfer the mixture with 10 mL of deionized water to a hydrothermal reactor and hydroheat it at 200°C for 10 h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, and dry the obtained solid in a vacuum oven at 100°C, transfer it to a tubular furnace, and then heat it to 750°C at a rate of 5°C / min in a nitrogen atmosphere, calcine it for 2 h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh) to prepare catalyst 26.
[0248] 2. Application of catalyst 26 in photocatalytic carbon dioxide reduction reaction.
[0249] Weigh 0.03 g of catalyst 26, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0250] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0251] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 2.8 μmol g -1 h -1 and 3.0 μmol g -1 h -1 .
[0252] Embodiment 22
[0253] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0254] Weigh 10 g of vinasse, add 20 g of 5% glutaraldehyde aqueous solution, ultrasonicate for 5 min, let stand for 35 min, add 15 mL of ferric chloride (1.5 mol / L), stir and mix evenly, magnetically stir at 40°C for 11 h, use 2 mol / L sodium hydroxide to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50°C for 10 h, put it in a microwave oven (power 500 W) for 3 min, and then transfer the mixture with 10 mL of deionized water to a hydrothermal reactor and hydroheat it at 200°C for 10 h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, dry the obtained solid in a vacuum oven at 100°C, transfer it to a tubular furnace, and then heat it to 750°C at a rate of 5°C / min in a nitrogen atmosphere, calcine it for 2 h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh) to prepare catalyst 27.
[0255] 2. Application of catalyst 27 in photocatalytic carbon dioxide reduction reaction.
[0256] Weigh 0.03 g of catalyst 27, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0257] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0258] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 2.8 μmol g -1 h -1 and 3.0 μmol g -1 h -1 .
[0259] Embodiment 23
[0260] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0261] Weigh 10 g of vinasse, add 20 g of 5% glutaraldehyde aqueous solution, ultrasonicate for 5 min, let stand for 35 min, add 15 mL of ferric sulfate (1.5 mol / L), stir and mix evenly, magnetically stir at 40°C for 11 h, use 2 mol / L sodium hydroxide to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50°C for 10 h, put it in a microwave oven (power 500 W) for 3 min, and then transfer the mixture with 10 mL of deionized water to a hydrothermal reactor and hydroheat it at 200°C for 10 h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, and dry the obtained solid in a vacuum oven at 100°C, transfer it to a tubular furnace, and then heat it to 750°C at a rate of 5°C / min in a nitrogen atmosphere, calcine it for 2 h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh) to prepare catalyst 28.
[0262] 2. Application of catalyst 28 in photocatalytic carbon dioxide reduction reaction.
[0263] Weigh 0.03 g of catalyst 28, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0264] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0265] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 1.2 μmol g -1 h -1 and 1.1 μmol g -1 h -1 .
[0266] Embodiment 24
[0267] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0268] Weigh 10g of vinasse, add 20g of 5% glutaraldehyde aqueous solution, ultrasonicate for 5min, let stand for 35min, add 15mL of ferrous oxalate (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, use 2mol / L sodium hydroxide to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 200℃ for 10h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, and dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 5℃ / min in a nitrogen atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh) to prepare catalyst 29.
[0269] 2. Application of catalyst 29 in photocatalytic carbon dioxide reduction reaction.
[0270] Weigh 0.03 g of catalyst 29, add sodium bicarbonate (0.84 g), evacuate the mixture, and then add 3.5 mL of 2 M sulfuric acid to generate CO2 and water in situ.
[0271] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0272] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 2.2 μmol g -1 h -1 and 1.8 μmol g -1 h -1 .
[0273] Embodiment 25
[0274] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0275] Weigh 10g of lees, add 20g of 5% glutaraldehyde aqueous solution, ultrasonicate for 5min, let stand for 35min, add 15mL of ferric nitrate (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, use 2mol / L sodium hydroxide to adjust the pH to greater than 9 to form a gel, vacuum dry it at -50℃ for 10h, put it in a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 200℃ for 10h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality, wash with ethanol 5 times, dry the obtained solid in a vacuum oven at 100℃, transfer it to a tubular furnace, and then heat it to 750℃ at a rate of 5℃ / min in a nitrogen atmosphere, calcine it for 2h, and obtain a black powder after cooling. Take it out and grind and sieve (100 mesh). The prepared catalyst 30.
[0276] 2. Application of catalyst 30 in photocatalytic carbon dioxide reduction reaction.
[0277] 0.03 g of catalyst 30 was weighed, sodium bicarbonate (0.84 g) was added, vacuum was applied, and 3.5 mL of 2 M sulfuric acid was added to generate CO2 and water in situ.
[0278] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0279] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 1.1 μmol g -1 h -1 and 1.0 μmol g -1 h -1 .
[0280] Table 7 Effects of different iron salts and concentrations
[0281]
[0282]
[0283] Comparative Example 8
[0284] 1. A method for preparing a nitrogen-phosphorus doped carbon material loaded with mixed-valence iron-based photocatalytic material:
[0285] Weigh 5g of biomass, add 20g of solvent, ultrasonicate for 5min, let stand for 35min, add 15mL of ferrous chloride (1.5mol / L), stir and mix evenly, magnetically stir at 40℃ for 11h, use 5mol / LKOH to adjust the pH to greater than 9 to form a green gel, put it into a microwave oven (power 500W) for 3min, and then transfer the mixture with 10mL of deionized water to a hydrothermal reactor and hydroheat it at 200℃ for 10h to obtain a solid-liquid mixture. After vacuum filtration, wash with deionized water to neutrality and ethanol for 5 times, the obtained solid is dried in a vacuum oven at 100℃, transferred to a tubular furnace, and then heated to 850℃ at a rate of 10℃ / min in a nitrogen atmosphere, calcined for 1.5h, and cooled to obtain a black powder. The powder is taken out and ground and sieved (100 mesh). The prepared catalyst 31.
[0286] 2. Application of catalyst 31 in photocatalytic carbon dioxide reduction reaction.
[0287] 0.02 g of catalyst 31 was weighed, sodium bicarbonate (0.84 g) was added, vacuum was applied, and 3.5 mL of 2 M sulfuric acid was added to generate CO2 and water in situ.
[0288] Then react under light (300W xenon lamp simulated sunlight) for 2 hours.
[0289] After the experiment, 0.5 mL of gas was extracted from the tube, and the peak area was detected by gas chromatograph (GC-14C) to calculate the CH4 or CO yield. The CH4 and CO production rates were 2.7 μmol g -1 h -1 and 2.1 μmol g -1 h -1 .
Claims
1. A method for preparing a biomass-derived in-situ nitrogen and phosphorus-doped carbon material loaded with an iron-based photocatalyst, characterized in that: The preparation method comprises the following steps: The biomass is weighed, crushed and ground to less than 200 meshes, a solvent is added, and after the biomass is fully dispersed and activated, an iron-containing aqueous solution is added, wherein the solute of the iron-containing aqueous solution is iron salt and / or ferrous salt and the total concentration is 0.5-3 mol / L, the mixture is stirred and mixed evenly, and then the pH is adjusted to be greater than 9 with an alkaline reagent to form a gel; the gel is freeze-dried, and then microwave-treated at a power of 400-800 W for 3-5 minutes, and then hydrothermally reacted at 160-200° C. for 8-15 hours, filtered and washed to obtain a precursor; after drying the precursor, the precursor is heated to 700-950° C. in an inert gas atmosphere at a heating rate of 3-15° C., calcined for 0.5-2.5 hours, and cooled to obtain a biomass-derived in-situ nitrogen-phosphorus-doped carbon material loaded with iron-based photocatalyst; The biomass is one or more selected from glucose, sucrose, brown sugar, soybean meal, Escherichia coli, yeast, humus, and distiller's grains; The alkaline reagent is any one or more of 1-6M ammonia water, 1-6M sodium hydroxide aqueous solution, 1-6M potassium hydroxide aqueous solution, 1-6M sodium carbonate aqueous solution, and 1-6M sodium bicarbonate aqueous solution; The feed ratio of the biomass, the solvent and the iron-containing aqueous solution is (2-10) g: (2-25) g: (10-40) mL.
2. The preparation method according to claim 1, characterized in that: The biomass is one of the following: a mixture of distiller's grains, yeast, soybean powder and humus in a mass ratio of 1:1, and a mixture of distiller's grains and brown sugar in a mass ratio of 5:
1.
3. The preparation method according to claim 1, characterized in that: The solvent is selected from any one of water, ethanol, 1-5 vol% glutaraldehyde aqueous solution, 1-5 vol% formaldehyde aqueous solution, and 1-5 vol% acetone aqueous solution; preferably, the solvent is selected from any one of water, 5 vol% glutaraldehyde aqueous solution, 3 vol% formaldehyde aqueous solution, and 5 vol% acetone aqueous solution.
4. The preparation method according to claim 1, characterized in that: The iron salt is any one or more of ferric chloride, ferric sulfate, and ferric nitrate, and the ferrous salt is any one or more of ferrous chloride, ferrous sulfate, ferrous acetate, and ferrous oxalate; preferably, the solute in the iron-containing aqueous solution is a ferrous salt, and more preferably any one of ferrous chloride, ferrous sulfate, and ferrous oxalate.
5. The preparation method according to claim 1, characterized in that: The temperature is raised to 750-850° C. at a rate of 3-10° C. / min in a nitrogen atmosphere, and calcined for 1-2 hours; more preferably, the temperature is raised to 750-850° C. at a rate of 5-10° C. / min in a nitrogen atmosphere, and calcined for 1-2 hours.
6. The preparation method according to claim 1, characterized in that: The biomass is vinasse or yeast, the solvent is 3% formaldehyde aqueous solution, 5% glutaraldehyde aqueous solution or 5% acetone aqueous solution, the iron-containing aqueous solution is 1.5M ferrous chloride aqueous solution, the alkaline reagent is 5M KOH aqueous solution or 5M ammonia water, and during the preparation process, the temperature is raised to 750-850°C in a nitrogen atmosphere at a rate of 3-10°C / min, and calcined for 1-2h; the feed ratio of the biomass, the solvent and the iron-containing aqueous solution is 5-10g:20g:15mL; most preferably: the biomass is vinasse, the solvent is 3% formaldehyde aqueous solution, the iron-containing aqueous solution is 1.5M ferrous chloride aqueous solution, the alkaline reagent is 5M KOH aqueous solution or 5M ammonia water, and during the preparation process, the temperature is raised to 850°C in a nitrogen atmosphere at a rate of 8-10°C / min, and calcined for 1-1.5h; the feed ratio of the biomass, the solvent and the iron-containing aqueous solution is 5-10g:20g:15mL.
7. The preparation method according to claim 1, characterized in that: The biomass is a mixture of soybean powder and humus in a mass ratio of 1:1, the solvent is water, the iron-containing aqueous solution is a 2.0M ferrous oxalate aqueous solution, and the alkaline reagent is 6M ammonia water. During the preparation process, the temperature is raised to 750°C in a nitrogen atmosphere at a rate of 5°C / min and calcined for 2h; the feed ratio of the biomass, the solvent and the iron-containing aqueous solution is 6g:30g:15mL.
8. A biomass-derived in-situ nitrogen and phosphorus-doped carbon material loaded with an iron-based photocatalyst prepared according to the preparation method of any one of claims 1 to 7.
9. The biomass-derived in-situ nitrogen and phosphorus-doped carbon material supported iron-based photocatalyst according to claim 8, characterized in that: The biomass-derived in-situ nitrogen and phosphorus-doped carbon material-loaded iron-based photocatalyst contains zero-valent, divalent and trivalent iron.
10. Use of the biomass-derived in-situ nitrogen and phosphorus-doped carbon material supported on an iron-based photocatalyst as claimed in claim 8 or 9 in photocatalytic reduction of CO2.
Citation Information
Patent Citations
Preparation methods and applications of nitrogen-containing defective Z-type carbon nitride-iron oxide catalysts
CN112371146B
Stable ternary composite material for hydrogen production by photocatalytic decomposition of water and preparation method thereof
CN112892607A
Coal-based carbon nanotube / activated carbon composite material for CH4 / N2 adsorption separation and preparation method of coal-based carbon nanotube / activated carbon composite material
CN117942942A
Biomass-based carbon aerogel material as well as preparation method and application thereof
CN118419898A
Preparation method of microbial-regulated composite metal oxide photocatalytic material and application of microbial-regulated composite metal oxide photocatalytic material in photocatalytic reduction reaction of carbon dioxide
CN118744008A